Strategic syntactic restructuring during simultaneous interpreting from Turkish into English - Hodzik, Ena; Özdemir, Semra; Conker, Nesrin; Bilgin, Orhan (Meta, 2024)
This study investigated the effects of contextual constraint and transitional probability on verb interpreting latency and syntactic restructuring during simultaneous interpreting from Turkish verb-final into English (verb-medial) sentences by trainee and professional Turkish (A)—English (B) interpreters. We found that contextual constraint, but not transitional probability, leads to both a decrease in interpreting latency on the sentence-final verb and a higher degree of syntactic restructuring between the source language input and target language output in both trainee and professional interpreters. Moreover, no between-group differences were observed in the effect of contextual constraint on verb interpreting latency and syntactic restructuring. The present findings suggest that, irrespective of experience, interpreters use contextual cues to restructure the word order between the source input and target output and produce the verb faster in the target output. This provides an argument for examining interpreting latency and syntactic restructuring together, as possible indicators of unvoiced anticipation during simultaneous interpreting between languages with dissimilar structures, such as Turkish and English.